Generation and characterization of chicken monocyte-derived dendritic cells - Ngantcha Tatchou, Elie; Milcamps, Romane; Oldenhove, Guillaume; Lambrecht, Bénédicte; Ingrao, Fiona (Frontiers in Immunology, 2025)
IntroductionDendritic cells (DCs) play a crucial role in orchestrating immune responses by bridging innate and adaptive immunity. In vitro generation of DCs from mouse and human tissues such as bone marrow and peripheral blood monocytes, has been widely used to study their immunological functions. In chicken, DCs have mainly been derived from bone marrow cell cultures, with limited characterization from blood monocytes.MethodsThe present study takes advantage of newly available chicken immunological tools to further characterize chicken monocyte-derived dendritic cells (MoDCs), focusing on their phenotype, and functions, including antigen capture and T-cell stimulation, and response to live Newcastle disease virus (NDV) stimulation.ResultsAdherent chicken PBMCs were cultured with recombinant chicken granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-4 (IL-4), for 5 days, leading to the upregulation of putative CD11c and MHCII, markers of DC differentiation. Subsequent stimulation with lipopolysaccharide (LPS) or 24 h triggered phenotypic maturation of MoDCs, characterized by the increased surface expression of MHCII and co-stimulatory molecules CD80 and CD40, and elevated IL-12p40 secretion. This maturation reduced endocytic capacity but enhanced the allogenic stimulatory activity of the chicken MoDCs. Upon NDV stimulation for 6 h, MoDCs upregulated antiviral pathways, including retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs), melanoma differentiation-associated protein 5 (MDA5) and laboratory of genetics and physiology 2 (LGP2), alongside increased production of type I interferons (IFNs), and the pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), IL-1β, and IL-6. However, these responses were downregulated after 24 hours.ConclusionThese findings provide a comprehensive characterization of chicken MoDCs and suggest their potential as a model for studying host-pathogen interactions.